2010
DOI: 10.1002/ajmg.b.31126
|View full text |Cite
|
Sign up to set email alerts
|

Risk gene variants for nicotine dependence in the CHRNA5CHRNA3CHRNB4 cluster are associated with cognitive performance

Abstract: Recent studies strongly support an association of the nicotinic acetylcholine receptor gene cluster CHRNA5-CHRNA3-CHRNB4 with nicotine dependence (ND). However, the precise genotype-phenotype relationship is still unknown. Clinical and epidemiological data on smoking behavior raise the possibility that the relevant gene variants may indirectly contribute to the development of ND by affecting cognitive performance in some smokers who consume nicotine for reasons of "cognition enhancement." Here, we tested seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 60 publications
6
51
1
1
Order By: Relevance
“…In a recent study, Winterer et al (2010) found a significant association between a functional variant, rs16969968, of the gene that encodes the a5 subunit of nAChRs (CHRNA5) and performance on the N-back working memory task that is consistent with the results of the aforementioned preclinical studies. The rs16969968 SNP has been associated with the age at which an individual initiates cigarette smoking, the severity of the nicotine dependence as measured by the Fagerström Test for Nicotine Dependence score, and the number of cigarettes that an individual smokes each day (Berrettini et al, 2008;Bierut et al, 2007;Saccone et al, 2007;Winterer et al, 2010).…”
Section: Other Nachrsupporting
confidence: 62%
See 3 more Smart Citations
“…In a recent study, Winterer et al (2010) found a significant association between a functional variant, rs16969968, of the gene that encodes the a5 subunit of nAChRs (CHRNA5) and performance on the N-back working memory task that is consistent with the results of the aforementioned preclinical studies. The rs16969968 SNP has been associated with the age at which an individual initiates cigarette smoking, the severity of the nicotine dependence as measured by the Fagerström Test for Nicotine Dependence score, and the number of cigarettes that an individual smokes each day (Berrettini et al, 2008;Bierut et al, 2007;Saccone et al, 2007;Winterer et al, 2010).…”
Section: Other Nachrsupporting
confidence: 62%
“…The rs16969968 SNP has been associated with the age at which an individual initiates cigarette smoking, the severity of the nicotine dependence as measured by the Fagerström Test for Nicotine Dependence score, and the number of cigarettes that an individual smokes each day (Berrettini et al, 2008;Bierut et al, 2007;Saccone et al, 2007;Winterer et al, 2010). These findings suggest that the vulnerability to nicotine dependence that is associated with this particular SNP may be mediated by a reduction in the cognitive performance of the individual.…”
Section: Other Nachrmentioning
confidence: 90%
See 2 more Smart Citations
“…Males from Cohort 2 underwent a battery of cognitive tasks (Winterer et al., 2010), of which the Continuous Performance Task (CPT) was most relevant to understanding attention. Key measures that were available from this sample included number of hits (i.e., responses to targets), false alarms (responses to non‐targets), and perceptual sensitivity ( D ′).…”
Section: Methodsmentioning
confidence: 99%